2014
DOI: 10.1088/0253-6102/62/5/01
|View full text |Cite
|
Sign up to set email alerts
|

Negativity of Quantumness and Non-Markovianity in a Qubit Coupled to a Thermal Ising Spin Bath System

Abstract: We propose a scheme to characterize the non-Markovian dynamics and quantify the nonMarkovianity via the non-classicality measured by the negativity of quantumness. By considering a qubit in contact with a critical Ising spin bath and introducing an ancilla, we show that revivals of negativity of quantumness indicate the non-Markovian dynamics. Furthermore, a normalized measure of non-Markovianity based on the negativity of quantumness is introduced and the influences of bath criticality, bath temperature and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(82 reference statements)
0
2
1
Order By: Relevance
“…As expected, the non-Markovian dynamics can be triggered when the intracollision strength is greater than a temperature-dependent threshold. In striking contrast to the usual understanding of the effect of the temperature on the non-Markovianity [58][59][60][61]63], we have found that the behavior of N as a function of T is non-monotonic, exhibiting a process of reduction and enhancement when temperature increases. In particular, we have shown that the non-Markovianity can vanish within a finite interval of T and then reappear when T increases.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As expected, the non-Markovian dynamics can be triggered when the intracollision strength is greater than a temperature-dependent threshold. In striking contrast to the usual understanding of the effect of the temperature on the non-Markovianity [58][59][60][61]63], we have found that the behavior of N as a function of T is non-monotonic, exhibiting a process of reduction and enhancement when temperature increases. In particular, we have shown that the non-Markovianity can vanish within a finite interval of T and then reappear when T increases.…”
Section: Discussioncontrasting
confidence: 99%
“…For a qubit subject to a dephasing bath with an Ohmic class spectrum, there exists a temperature-dependent critical value of the Ohmicity parameter for the onset of non-Markovianity which increases for high temperatures [58]. For a qubit in contact with a critical Ising spin thermal bath it has been then shown that the non-Markovianity decreases close to the critical point of the system in such a way that the higher the temperature, the higher the decrease [59]. Moreover, it is known that the non-Markovianity of a chromophore qubit in a super-Ohmic bath is reduced when the temperature increases [60].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the system can retrieve some information lost during the evolution of the system. In recent years, the study of non-Markovian dynamics has attracted extensive attentions and becomes a topical field [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], particularly in the characterization and measure of non-Markovianity [22][23][24][25][26][27][28][29][30][31]. For example, the Breuer, Laine, and Piilo (BLP) measure [29] is proposed based on the trace distance which quantifies the degree of distinguishability between two arbitrary different initial states.…”
Section: Introductionmentioning
confidence: 99%